Differential item functioning between ethnic groups analysed in the context of multimodal learning - Chiang, Lian Hwa. (2009)
This paper was an attempt to study differential item functioning in Mathematics between two groups of students from different ethnic and cultural backgrounds. Three different statistical methods were employed to flag items that were differentially functioning. The three methods were: 1 The Mantel-Haenszel Method 2 A Logistic Regression Method 3 An IRT-LR method, namely the one as implemented by BILOG-MG